APPLICATION OF FAILURE TREE FOR ANALYSIS OF ELECTROTRAUMATISM IN METALLURGY AND CHOICE OF PROTECTIVE EQUIPMENT - Ryzhkov, Vadim; Belokon, Karina; Manidina, Eugene (Scientific Journal "Metallurgy", 2022)
lectric injuries at work are highly lethal, which requires careful compliance with the rules and regulations of electrical safety, the use of protective equipment. Any metallurgical enterprise has an extensive electrical network, a significant number of electricity consumers. In addition, unfavorable working conditions and the presence of factors of increased and special risk of electric shock are added here. All of the above have increased requirements for electrical safety. Of great importance for the prevention of electrocution is the study of statistics, the identification of the immediate causes of electric shock and a number of events that often lead to an accident. One of the methods of risk assessment is the method of constructing a failure tree. The failure tree is a graphical model of various parallel and sequential combinations of failures that lead to the implementation of a predetermined adverse event. Failures – base events can be events related to the failure of system elements, personnel errors, equipment unpreparedness. A failure tree has been constructed in which the top, undesirable event is the electric shock of a person at work during the year. Various equipment problems, lack or failure of means of protection, violation of safety rules by personnel, etc. were taken as basic events. Based on the constructed failure tree, the probability of electric shock was calculated, the most dangerous series of events leading to an accident were identified. Analysis of the result of the calculation showed that to reduce the risk of electric shock, it is necessary, first of all, to prevent erroneous voltage supply, or to minimize this possibility. As a technical measure it is possible to offer blocking of devices of switching on of current during carrying out repair work. It is important to ensure the reliability of the protective earthing or grounding. Practice shows that the reliability of protection against electric shock is significantly increased if a protective circuit breaker is connected in parallel to grounding (zeroing).